2001
DOI: 10.1021/ie000997e
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Primary Product Formation from Wood Pyrolysis

Abstract: Weight loss curves of thin layers (150 μm) of beech wood powder, measured for heating rates of 1000 K/min and final temperatures in the range 573−708 K, show final char yields of 37−11%. The process is kinetically controlled and, for the most part, isothermal. A one-step global reaction, with E = 141.2 ± 15.8 kJ/mol and ln A = 22.2 ± 2.9 s-1, is a degradation mechanism capable of capturing the main features of the process. The thermogravimetric curves also allow the formation rate constants to be estimated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
122
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(134 citation statements)
references
References 47 publications
11
122
1
Order By: Relevance
“…They showed that higher reaction temperature (800 to 1000°C) led to lower yields of tars and higher yields of gaseous products. In addition, pyrolysis of smaller particles (0.5 to 1 mm) improved the char reactivity for combustion or gasification [20]. Results found by Guerrero et al [1] showed that the reactivity to oxygen of the char produced by eucalyptus pyrolysis increases with the heating rate of biomass particles.…”
Section: Introductionmentioning
confidence: 93%
“…They showed that higher reaction temperature (800 to 1000°C) led to lower yields of tars and higher yields of gaseous products. In addition, pyrolysis of smaller particles (0.5 to 1 mm) improved the char reactivity for combustion or gasification [20]. Results found by Guerrero et al [1] showed that the reactivity to oxygen of the char produced by eucalyptus pyrolysis increases with the heating rate of biomass particles.…”
Section: Introductionmentioning
confidence: 93%
“…At present, many simplified reaction mechanisms exist for the study of biomass pyrolysis. These are either one-step global models (15)(16)(17)(18)(19) or one-or two-stage multiple reaction models (20,(21)(22)(23)(24)(25)(26) . Di Blasi (27) and Prakash and Karunanithi (28) have given some comprehensive reviews of advances in modeling and simulation of chemical and physical processes of wood and biomass pyrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Fixed bed reactors have been used in some experiments, and they can process from 10 to 500 g of material (Deng et al 2009;Kim et al 2012;Oliveira and Rousset 2009;Prins et al 2006b). Finally, fluidized systems have been designed to study the thermal kinetic decomposition of wood by Barooah and Long (1976), Di Blasi and Branca (2001), and Peng et al (2012). Barooah and Long (1976) presented results for the rates of thermal decomposition of beech sawdust in a fluidized reactor, using heated sand to raise the biomass temperature.…”
Section: Introductionmentioning
confidence: 99%
“…They obtained a kinetic model of a first-order reaction for temperatures ranging between 250 and 330 °C; when they increased the temperature over 330 °C, a second-order kinetic model was found to be consistent with the data. Di Blasi and Branca (2001) published a study on the kinetic parameters for beech decomposition in a fluidized reactor at higher temperatures (between 300 and 435 °C). The main results indicated that a one-step global reaction is capable of adequately modeling the torrefaction process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation